Develop a real-time concentration sensor for LDDS - Xu, Meilan. (2013)
In a Liquid Desiccant Dehumidification System (LDDS), the concentration of desiccant solution plays an important role on the efficiency of moisture absorption. The extraction of moisture from air will result in the dilution of the desiccant solution, thus decrease the dehumidification ability of the system. To restore the solution back to initial concentration, the weak solution needs to be heated in Regeneration Unit and then pumped back to the Dehumidification Unit. To maintain such continuous cycle, a discrete real-time concentration sensor is developed to monitor the concentration changes. Modifying from the float switch, this sensor is also able to monitor the low and high level of desiccant solution in the tank. This report also includes the performance testing of the sensor.